El nuevo orden multipolar del siglo XXI y la consolidación de bloques regionales: oportunidades para Unasur y la integración Suramericana - Granda Garrido, André Mauricio (2015)
The XXI century brought fundamental changes in the international system and global power relations. After the end of the Cold War, the world has witnessed the consolidation of the United States as the sole superpower in the world, thus forming a unipolar international order. However, developments in international politics are never static, and the durability of unipolarity has been threatened by rising actors and systemic circumstances which show the progressive consolidation of a new international order in the twenty-first century. The end of unipolarity has given way to a multipolar world shaped by various powers and their respective areas of influence or regional blocs. In this new multipolar context, unique opportunities arise for Latin American countries to acquire a leading role on the international stage. The central idea of this work is that in order to take advantage of this historic moment, the countries of South America should be consolidated as a single regional bloc of influence, through the Union of South American Nations, UNASUR, and the convergence of integration mechanisms already existing…